INTERESSE E ATITUDE DOS ESTUDANTES DE ADMINISTRAÇÃO E CIENCIAS CONTÁBEIS EM RELAÇÃO ÀS DISCIPLINAS DE FORMAÇÃO BÁSICA - Nilson dos Santos Dias (Revista Gestão Universitária na América Latina, 2017)
The academic training of management courses and accountancy provides that the graduate has analytical skills, understanding and finding solutions to social problems, in the face of it, the course curriculum search offer training in general knowledge and human. This study aims to identify the level of interest of bachelor's degree students in Accounting and Administration Sciences in relation to basic training disciplines that are essenti al in their training. From the use of a model based on the literature, the factors were investigated that influence the student's interest, making use of a questionnaire applied to 455 students of both courses. The data collected were subjected to techniqu es of descriptive statistics univariate (descriptive statistics, factor analysis and linear regression). As a result of this analysis it was found that the skills, the perceived importance of discipline, the perceived difficulty and confidence positively i nfluence the student's interest by the general education disciplines.